Duodenal neuroendocrine neoplasms with unexpectedly aggressive behaviour: Challenging the "watch and wait" approach. (16th December 2021) - Ratnayake, Gowri M.; Srirajaskanthan, Raj; Luong, TuVinh; Gnanasegaran, Gopinath; Toumpanakis, Christos
Abstract: The incidence of duodenal neuroendocrine neoplasms has risen over the past decades as a result of the wide availability of endoscopy and associated expertise. Although it is considered that tumour size greater than 10 mm, higher tumour grade and/or location in relation to the ampulla of Vater represent the main risk factors for local or distant metastases, we describe two cases of well differentiated grade 1 and grade 2 neuroendocrine tumours, which measured < 10 mm at the time of diagnosis but had an aggressive course during follow‐up. Furthermore, we also summarise the available therapeutic strategies for the management of small, low grade, non‐functioning, non‐ampullary duodenal neuroendocrine neoplasms.